PENDUGAAN RESERVOIR DAERAH POTENSI PANAS BUMI PENCONG DENGAN MENGGUNAKAN METODE TAHANAN JENIS - Erwin Erwin (Universitas Negeri Makassar, 2016)
Research on prediction of geothermal area reservoir at Pencong aimed to determine the position of geothermal reservoir by using geoelectric resistivity method in geothermal area of Pencong Gowa. This study used geoelectric resistivity method with Schlumberger configuration. Measurement at location was done by using GPS equipment and resistivitymetre Naniura NRD 22 S with 5 points sounding. Data obtained in the form of current value, potential difference, and the coordinate position of the measuring area. Data processing was performed by using Microsoft Excel program and IP2win software. The results showed that at the location of research, there exist geothermal reservoir at the point of sounding 4 at a depth of 21.5-46.4 meters and at sounding point 5 at a depth of 16.7-46.4 meters. At the locations, there was suspected argillaceous sandstones as geothermal reservoirs.Keywords: IP2win, Schlumberger configuration, geothermal reservoir, resistivityPenelitian tentang pendugaan reservoir daerah panas bumi Pencong bertujuan untuk menentukan posisi reservoir panas bumi dengan metode geolistrik tahanan jenis pada daerah panas bumi Pencong Kabupaten Gowa. Penelitian ini menggunakan metode geolistrik tahanan jenis konfigurasi Schlumberger. Pengukuran ini dilakukan di lapangan menggunakan peralatan GPS dan Resistivitymeter merek Naniura NRD 22 S dengan 5 titik sounding. Data yang diperoleh berupa nilai arus, beda potensial, dan koordinat posisi daerah pengukuran. Pengolahan data dilakukan dengan menggunakan program Microsoft Excel dan software IP2win. Hasil pengolahan data menunjukkan bahwa pada lokasi penelitian terdapat reservoir panas bumi di titik sounding 4 pada kedalaman 21.5-46.4 meter dan titik sounding 5 pada kedalaman 16.7-46.4 meter, dimana terdapat batu pasir berlempung diduga sebagai reservoir panas bumi.Kata Kunci: IP2win, konfigurasi Schlumberger, reservoir panas bumi, resistivitas